Chronic Myeloid Leukemia: Etiology, Risk Factors, Pathophysiology, Diagnosis, Management, and Prognosis - Patandianan, Firdaus Kamma; Hasanah, Mielosita; Mikaila, Romy Healthy; Athalia, Ihza Namira; Nitzana, Lale Nubya; Hairy, Fathinah Salsabila (Jurnal Biologi Tropis, 2025)
The Philadelphia chromosome is a hallmark of Chronic Myeloid Leukemia (CML), a hematopoietic stem cell disease caused by the reciprocal translocation t(9;22)(q34;q11) that creates the oncogenic fusion gene BCR-ABL1, which persistently activates tyrosine kinase and encourages unchecked myeloid cell proliferation. This literature review aims to describe the pathophysiology, clinical manifestations, diagnosis, treatment, and prognosis of CML based on recent studies. Literature searches were conducted through PubMed, Google Scholar, and official institutional websites using the keywords “Chronic Myeloid Leukemia,” “Philadelphia chromosome,” and “BCR-ABL1.” CML accounts for approximately 15–20% of all leukemia cases and progresses through three phases: chronic, accelerated, and blast crisis. The BCR-ABL1 fusion gene constitutively activates multiple oncogenic pathways, including JAK/STAT, PI3K/AKT, and RAS/RAF, leading to enhanced proliferation and resistance to apoptosis. Diagnosis is established through hematologic examination and molecular testing using PCR or FISH for BCR-ABL1 detection. The mainstay treatments include tyrosine kinase inhibitors such as imatinib, dasatinib, and nilotinib, with stem cell transplantation reserved for advanced cases. With early diagnosis and appropriate therapy, overall survival exceeds 80% at eight years. In conclusion, CML is a chronic hematologic malignancy driven by BCR-ABL1, and advances in molecular-targeted therapy have transformed it into a manageable chronic disease with significantly improved patient outcomes.